Pengaruh Tingkat Perputaran Kas dan Piutang Terhadap Rentabilitas pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar Dibursa Efek Indonesia Tahun 2018-2021 - Rifqi, Muhammad; Rina Asmeri; Sri Yuli Ayu Putri (Fakultas Ekonomi, Universitas Ekasakti, 2024)
Profitability is an illustration of a company's progress which can be seen from the level of cash and receivables turnover. This research aims to determine and analyze the effect of the level of cash and receivables turnover on profitability in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021, either partially or simultaneously. The type of data used in the research is quantitative data sourced from annual financial reports sourced from annual reports. The data source in this research is secondary data. The population in this study were sub-food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021 with a total of 36 samples. The sampling technique used purposive sampling technique according to the specified criteria and obtained 36 companies. The data analysis method in this research uses multiple linear regression. Based on the results of the partial analysis, it is known that the results of the cash turnover rate have a significant effect on profitability. And the level of receivables turnover partially has a significant influence on profitability. And the level of cash turnover and receivables simultaneously has a significant effect on profitability in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021.